1988
DOI: 10.1002/fut.3990080106
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐strong test of the efficiency of the aluminum and copper markets at the LME

Abstract: market is defined to be efficient if there exists no profitable trading strategy. This has to hold even if all currently available information about the market (excluding inside information) has been skillfully used. The question of whether or not a market satisfies this criterion is of considerable interest as participants can engage in efficient markets at less transaction costs as in markets which necessitate extensive information search.For a commodity which is traded on spot and on futures markets, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…Canarella and Pollard (1986), Gross (1988), andMacDonald andTaylor (1988) found that the LME was efficient, while Kenourgios and Samitas (2004) and Otto (2011) found opposing results. Goss (1985) tested the joint hypothesis of spot and futures prices on the LME from 1966 to 1984.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Canarella and Pollard (1986), Gross (1988), andMacDonald andTaylor (1988) found that the LME was efficient, while Kenourgios and Samitas (2004) and Otto (2011) found opposing results. Goss (1985) tested the joint hypothesis of spot and futures prices on the LME from 1966 to 1984.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Any strategy, therefore, designed to enhance the long-term profitability of trading LME futures may not succeed as long as the market is efficient. Gross (1988) tested the semi-strong EMH for copper and aluminum from 1983 to 1984 using the mean square error criterion. He found that the semi-strong EMH could not be rejected for both base metals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They rejected the EMH for tin and zinc. Gross [11] examined unvaried LME prices on the mean square error criterion for the period 1983-1984 in order to test the semi-strong EMH for copper and aluminium futures. He provided evidence that the semi-strong EMH cannot be rejected for both base metals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gross (1988) (Gross,19(8). Gross, however, takes issue with this conclusion on the basis that ne't1T information becoming available could cause the prices of several metals to move in the same direction, leading to correlation in the forecasting errors.…”
Section: Efficiency Of Copper Marketsmentioning
confidence: 99%